2013
DOI: 10.1111/jocn.12474
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' knowledge of evidence‐based guidelines on the prevention of peripheral venous catheter‐related infections: a multicentre survey

Abstract: These data request for more emphasis on international guidelines in infection prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
3
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 58 publications
7
78
3
17
Order By: Relevance
“…It claimed that this low level of knowledge could be a potential risk factor for patient's safety [35].…”
Section: Discussionmentioning
confidence: 99%
“…It claimed that this low level of knowledge could be a potential risk factor for patient's safety [35].…”
Section: Discussionmentioning
confidence: 99%
“…As IV set changes are predominantly a nursing responsibility, it is important to determine nurses' current practice before attempting to implement a policy or practice change. Although nurses' decisions regarding adherence to clinical guidelines and whether to leave or remove IV devices have been investigated and reported in the literature (Cicolini et al, ; Jeffery & Pickler, ; Johansson, Pilhammar, Khalaf, & Willman, ; Johansson, Pilhammar, & Willman, ; Palese et al, ), nurses' decision‐making regarding administration set replacement has not been previously assessed. Understanding the knowledge and practical considerations underpinning clinical decision‐making is a vital component of laying the groundwork for knowledge translation (Yost et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The latest knowledge of nurses in the implementation of daily clinical practice is essential for the safety of the application of nursing procedures [12].In this study, only 60% of the sample of nurses responded to the questions of knowledge and skills of nurses hand washing during the nursing care of pediatric patients. Even a percent of 80.0% of the sample declared to have been trained in hospital for hand washing technique while 17.8% no, it was found that only one third did not own the acceptable level of knowledge of the technique of hand washing.…”
Section: Discussionmentioning
confidence: 75%